Attitudes to Natural Phenomena in Rome during the Late Republic - Graham, Daryn (Cosmos and History: The Journal of Natural and Social Philosophy, 2022)
Natural phenomena were part of ancient Rome’s human history, and altered the political scene, the cityscape, and religious practice and belief throughout society, to a great extent. Over time, natural disasters in Rome came to be thought of in terms of poetic verse, and making capital, especially among Lucretius, Cicero, and Crassus. However, they were always nuisances and a threat to public and private space, as well as human and animal life. In this article, it is shown that natural phenomena gave much cause for pause and reflection, and writing and action. It will also be shown that while some remained true to long-held philosophies regarding these, others were willing to change their minds, over time.